The Unruh effect and its applications - Crispino, Luís C. B.; Higuchi, Atsushi; Matsas, George E. A. [UNESP] (American Physical Society (APS), 2008)
It has been 30 years since the discovery of the Unruh effect. It has played a crucial role in our understanding that the particle content of a field theory is observer dependent. This effect is important in its own right and as a way to understand the phenomenon of particle emission from black holes and cosmological horizons. The Unruh effect is reviewed here with particular emphasis on its applications. A number of recent developments are also commented on and some controversies are discussed. Effort is also made to clarify what seem to be common misconceptions. © 2008 The American Physical Society.